Playfulness and Playful Work Design Among Early Childhood Educator : Teacher Well-Being as Mediator - Dearly, Dearly; Mardhatillah, Amy; Intan Savitri, Setiawati; Fitriana, Mimi (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
Individuals across various occupations, including teaching, can incorporate play into their tasks to make their work more enjoyable, and this approach is known as playful work design. Personality traits influence how individuals approach their work, but there is limited research on how positive traits like playfulness relate to playful work design, especially for early childhood teachers. This study investigates the role of playfulness in fostering playful work design, with teacher well-being as a mediator. Data were collected from 358 early childhood teachers using the Adult Playfulness Trait Scale (APTS), the Playful Work Design Scale, and the Teacher Well-Being Scale (TWBS). The analysis used Structural Equation Modelling (SEM) with Jamovi software. The results show that teacher well-being partially mediates the relationship between playfulness and playful work design. While playfulness directly affects playful work design, the effect is weak. In contrast, teacher well-being is much stronger in influencing playful work design. These findings highlight the importance of addressing personality traits and well-being to create enjoyable and effective work environments in early childhood educational settings.